2013
DOI: 10.1136/bmjopen-2013-003787
|View full text |Cite|
|
Sign up to set email alerts
|

Geographical prevalence and risk factors for pterygium: a systematic review and meta-analysis

Abstract: ObjectivePterygium is considered to be a proliferative overgrowth of bulbar conjunctiva that can induce significant astigmatism and cause visual impairment; this is the first meta-analysis to investigate the pooled prevalence and risk factors for pterygium in the global world.DesignA systematic review and meta-analysis of population-based studies.SettingInternational.ParticipantsA total of 20 studies with 900 545 samples were included.Primary outcome measureThe pooled prevalence and risk factors for pterygium.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
143
1
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(166 citation statements)
references
References 30 publications
9
143
1
13
Order By: Relevance
“…This is probably due to males forming majority (68.00%) of the study sample. Several studies have reported gender to be an independent predictor of pterygium, with males more likely to develop pterygium than females [15,17,20,24,29,[34][35][36][37]. The Tanjong Pagar survey reported males to be five times more likely to develop pterygium than females [38].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is probably due to males forming majority (68.00%) of the study sample. Several studies have reported gender to be an independent predictor of pterygium, with males more likely to develop pterygium than females [15,17,20,24,29,[34][35][36][37]. The Tanjong Pagar survey reported males to be five times more likely to develop pterygium than females [38].…”
Section: Resultsmentioning
confidence: 99%
“…Ultraviolet (UV) light exposure is believed to be the single most important risk factor for development of pterygium [26]. Individuals with increased UV light exposure such as outdoor workers (farmers, welders, surfers, fishers, gardeners etc) have an increased risk of pterygium development compared to indoor workers [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence of this connective tissue growth over cornea in this population (26.2%) was much higher than the worldwide rate (10.2%). [39] Very few published studies reported greater prevalence of pterygium: 33.01% in Doumen County, China [40]; 30.8% in Kumejima Island, Japan [41]; and 36.6% in Arawak and Tukano indian communities from Amazon forest [42]. Rural environment, low geographical latitude of Conceição das Crioulas and preponderance of black ethnicity among quilombolas may contribute to the high prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Rural environment, low geographical latitude of Conceição das Crioulas and preponderance of black ethnicity among quilombolas may contribute to the high prevalence. [39,43] Other probable contributing factors to numerous cases of pterygium, not evaluated in this study, are: outdoor work, few years of education, low use of protection to UV exposure (hat, sunglasses or prescription glasses). Three quilombolas were referred to pterygium surgery.…”
Section: Discussionmentioning
confidence: 99%